Single-Port Coherent Perfect Loss in a Photonic Crystal Nanobeam Resonator - Jihoon Choi; Heeso Noh (Nanomaterials, 2021)
We numerically demonstrated single-port coherent perfect loss (CPL) with a Fabry–Perot resonator in a photonic crystal (PC) nanobeam by using a perfect magnetic conductor (PMC)-like boundary. The CPL mode with even symmetry can be reduced to a single-port CPL when a PMC boundary is applied. The boundary which acts like a PMC boundary, here known as a PMC-like boundary, and can be realized by adjusting the phase shift of the reflection from the PC when the wavelength of the light is within the photonic bandgap wavelength range. We designed and optimized simple Fabry–Perot resonator and coupler in nanobeam to get the PMC-like boundary. To satisfy the loss condition in CPL, we controlled the coupling loss in the resonator by modifying the lattice constant of the PC used for coupling. By optimizing the coupling loss, we achieved zero reflection (CPL) in a single port with a PMC-like boundary.